The Palgrave Handbook of Languages and Conflict - Kelly, Michael; Footitt, Hilary; Salama-Carr, Myriam; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This Handbook maps the contours of an exciting and burgeoning interdisciplinary field concerned with the role of language and languages in situations of conflict. It explores conceptual approaches, sources of information that are available, and the institutions and actors that mediate language encounters. It examines case studies of the role that languages have played in specific conflicts, from colonial times through to the Middle East and Africa today. The contributors provide vibrant evidence to challenge the monolingual assumptions that have affected traditional views of war and conflict. They show that languages are woven into every aspect of the making of war and peace, and demonstrate how language shapes public policy and military strategy, setting frameworks and expectations. The Handbook's 22 chapters powerfully illustrate how the encounter between languages is integral to almost all conflicts, to every phase of military operations and to the lived experiences of those on the ground, who meet, work and fight with speakers of other languages. This comprehensive work will appeal to scholars from across the disciplines of linguistics, translation studies, history, and international relations; and provide fresh insights for a broad range of practitioners interested in understanding the role and implications of foreign languages in war. Michael Kelly is Emeritus Professor of French at the University of Southampton, UK. Hilary Footitt is Senior Research Fellow in the University of Reading, UK. Myriam Salama-Carr is Honorary Research Fellow in Translation and Interpreting at the University of Manchester, UK.
Introduction: The Shock of War; Michael Kelly, Hilary Footitt, Myriam Salama-Carr -- Part One. Conceptual Spaces. Good Anthropology, Bad History: America's Cultural Turn in the War on Terror; Patrick Porter -- On Encounters and Ethics in the Vietnam War; Moira Inghilleri -- From the Page to the Battlefield: Translating War; Myriam Salama-Carr -- Language Policy and War; Michael Kelly -- Part Two. Source, documentation and voices -- Military History and Translation Studies: Shifting Territories, Uneasy Borders; Hilary Footitt, Pekka Kujamäki -- Archives and Sources; Hilary Footitt -- Interviewing for research on languages and war; Catherine Baker -- Part Three. Institutions and Actors -- Interpreting in Peace and Conflict: Origins, Developing Practices and Ethics; Linda Fitchett -- Interpreters at war: Testing boundaries of neutrality; Fabrizio Gallai -- Providing Language Support for NATO Operations: Challenges and Solutions; Louise Askew -- Translation and Open Source Intelligence: BBC Monitoring; Laura Johnson -- Covering regional conflicts in Arab news: Political loyalties and hate speech; Zahera Harb -- Uncompromising talk, linguistic grievance, and language policy: Thailand's Deep South conflict zone; Joseph Lo Bianco -- Transnational Institutions: War Crimes Tribunals; Ellen Elias- Bursać -- Part Four. Languages at War in history -- Colonial conflict and imperial rivalries in the Americas; Roberto A. Valdeón -- The British in the Second World War: translation, language policies and language practices; Hilary Footitt -- Understanding interpreting and diplomacy: reflections on the early Cold War (1945-1963); María Manuela Fernández Sánchez -- Colonial heritage, identity-building and communication: English and Nigerian languages in Biafra; Françoise Ugochukwu -- Linguistic unrest at times of revolution: The case of Tunisia, Egypt, and Libya; Reem Bassiouney -- Who really wants to learn Arabic?; Yonatan Mendel -- Part Five. Going Forward: Conclusions and Reflections -- Languages and new forms of warfare; Michael Kelly -- Looking Ahead: Conclusions and Reflections; Michael Kelly, Hilary Footitt, Myriam Salama-Carr.
Keywords: Applied linguistics; Sociolinguistics; Translating and interpreting; Peace; Language policy; Applied Linguistics; Sociolinguistics; Language Translation; Peace and Conflict Studies; Language Policy and Planning